2001
DOI: 10.1021/jp002503x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Orientation in Vacuum-Deposited Peralkyloligosilane Thin Films

Abstract: Linear oligosilanes (R(SiR2)10R), permethyldecasilane (R = CH3), and perpropyldecasilane (R = C3H7), were vacuum-deposited onto quartz substrates under various conditions. Molecular orientation in the deposited thin films was investigated by X-ray diffractometry and absorption spectroscopy with a varying incident angle to the substrate. Two types of highly ordered multilayered structures, one with molecular orientation normal to the substrate and the other with oblique orientation, were observed in the permeth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…Absorption spectra collected above 340 K with every 10 K step are shown in Figure . Prior to the annealing study, we confirmed that the absorption spectrum of the vacuum-deposited MS10 thin film hardly depended on the temperature from 15 to 340 K. This result is presumably explained in terms of the well-organized multilayered structure, in which the molecules were tightly packed and, hence, their conformation as well as their alignment was fixed below 340 K. The spectral profile slightly changed when heated to 350 K, because of the increase of the absorbance around 300 nm.
1 Absorption spectra of the vacuum-deposited MS10 thin film at elevated temperatures from 340 to 370 K and at 320 K after annealing.
…”
Section: Resultssupporting
confidence: 60%
See 3 more Smart Citations
“…Absorption spectra collected above 340 K with every 10 K step are shown in Figure . Prior to the annealing study, we confirmed that the absorption spectrum of the vacuum-deposited MS10 thin film hardly depended on the temperature from 15 to 340 K. This result is presumably explained in terms of the well-organized multilayered structure, in which the molecules were tightly packed and, hence, their conformation as well as their alignment was fixed below 340 K. The spectral profile slightly changed when heated to 350 K, because of the increase of the absorbance around 300 nm.
1 Absorption spectra of the vacuum-deposited MS10 thin film at elevated temperatures from 340 to 370 K and at 320 K after annealing.
…”
Section: Resultssupporting
confidence: 60%
“…Figure exhibits an intense series of diffraction peaks labeled with 00 l ( l = 1−5), indicating the highly ordered multilayered structure with an interlayer spacing of 20.9 Å. Very recently, we have proposed normal molecular orientation in such multilayered structure on the basis of the comparison between the interlayer spacing and the molecular length with all-trans conformation . After annealing, another peak series labeled with 00 l ‘ ( l ‘ = 1−6) appeared, corresponding to another multilayered structure with an interlayer spacing of 18.5 Å.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…Nakayama et al reported that the oriented polysilane film shows higher hole transport ability than the nonoriented one . The main chain of the PDMS molecule was reported to be oriented vertically to the substrate thin film prepared by the vacuum deposition on a quartz plate. To confirm molecular orientation of PDMS in the composite film, the absorption spectra of J O−H−Cl /PDMS composite film were measured at the angle θ of 0° and 50°, where θ is the angle between the normal to the substrate and irradiation direction (Figure a). At θ of 50°, the absorption band due to the σ−σ* transition of the main chain was observed at 295 nm.…”
Section: Resultsmentioning
confidence: 99%